Cardiovascular disease in out-patient practice of therapeutists and cardiologists - L. A. Bokeria; I. N. Stupakov; I. V. Samorodskaya; E. N. Fufaev; E. V. Bolotova (Кардиоваскулярная терапия и профилактика)
Aim. To study the structure of cardiovascular disease (CVD) and prevalence of comorbidity, the needs for diagnostics and treatment methods in out-patient practice of cardiologists and therapeutists.Material and methods. The study involved polyclinic-based cardiologists and therapeutists from 5 subjects of the Russian Federation. During 3 consecutive days, the doctors enrolled male and female patients aged over 18 years, with one or several CVD and/or congenital valve pathology (CVP). Individual registration forms (IRFs), completed for each patient, were mailed to A.N. Bakulev Research Center for Cardiovascular Surgery. All data were centrally processed. Out of 6312 scanned IRFs, 3982 were selected (63,1 %; 95 % CI 61,9–64,3) and analyzed as one sample and by 3 nosological groups: coronary heart disease (CHD), CVP, acquired valve pathology.Results. Among out-patients, combined pathology (CVD and comorbidity) was widely prevalent. The combination of CHD and arterial hypertension (AH) was observed in 34 %, of CHD, AH and other CVD – in 28 %. The most prevalent comorbidities were diabetes mellitus (19 %) and chronic obstructive pulmonary disease (9 %). Comorbidity prevalence was associated with the main diagnosis and age. Leading reasons for seeking medical help were disease exacerbation and need for prescription during remission period (59 %). According to doctors’ opinion, the main indication for diagnostic procedures was “controlling the patient’s status”. At present, methodology of assessing the need for surgical and endovascular interventions among CVD patients is not standardised. In most out-patients (71,7 %), main income source is social subsidies. It could be expected that even in the future, federal budget subsidies will dominate in the payments for high-technology medical service.Conclusion. The study results reflect social and clinical characteristics of CVD and CVP patients, as well as primary healthcare doctors’ views on the need for diagnostic and therapeutic interventions.